Downward trend in prevalence of intestinal parasites in children over two decades, southern Brazil (Research, Society and Development, 2022)
About one-quarter of the world's population is infected by geohelminths. The aim of this research was investigated the prevalence and predictors associated with intestinal parasites in children on over two decades. A retrospective study was conducted with children (0-18 years old) attended in the period of 1997-2016 by a public institution in southern Brazil. Data analysis was carried out using Stata® 9.1. A total of 7,292 records were analyzed; the overall prevalence was 25.5%. Most records showed infection by protozoa (69.4%). The most prevalent intestinal parasites were Entamoeba coli (9.4%) and Giardia duodenalis (8.9%). Statistically significant (p